1991
DOI: 10.1073/pnas.88.1.26
|View full text |Cite
|
Sign up to set email alerts
|

NMR and molecular modeling evidence for a G.A mismatch base pair in a purine-rich DNA duplex.

Abstract: ABSTRACT1H NMR experiments indicate that the oligomer 5'-d(ATGAGCGAATA) forms an unusual 10-base-pair duplex with 4 G-A base pairs (underlined) and a 3' unpaired adenosine. NMR results indicate that guanosine imino protons of the G-A mismatches are not hydrogen bonded but are stacked in the helix. A G -* I substitution in either G-A base pair causes a dramatic decrease in duplex stability and indicates that hydrogen bonding of the guanosine amino group is critical. Nuclear Overhauser effect spectroscopy (NOESY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
98
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(108 citation statements)
references
References 30 publications
10
98
0
Order By: Relevance
“…A remaining possibility is the amino-paired G . A structures previously observed in DNA (Li et al, 1991Lane et al, 1992). A feature of this pairing in DNA is that the amino-pairing occurs only in the sequence context YGAR Cheng et al, 1992), and does not significantly destabilise the DNA duplex.…”
Section: Conformationmentioning
confidence: 84%
See 3 more Smart Citations
“…A remaining possibility is the amino-paired G . A structures previously observed in DNA (Li et al, 1991Lane et al, 1992). A feature of this pairing in DNA is that the amino-pairing occurs only in the sequence context YGAR Cheng et al, 1992), and does not significantly destabilise the DNA duplex.…”
Section: Conformationmentioning
confidence: 84%
“…In DNA, the sequences that contain YGAR have been shown to have amino pairing of the G . A mismatches Lane et al, 1992;Chou et al, 1992) as first identified by Li et al (1991). All of the other sequences have the mismatched bases paired in the imino form.…”
Section: Thermodynamicmentioning
confidence: 99%
See 2 more Smart Citations
“…The competing wild-type PNA oligomer covered codons 10 -14. The antisense strand was chosen for the PNA oligomer and the detection probes because of its lower purine content and, therefore, more precise hybridization results (24 ). The primers, probes, and the PNA oligomer were from TIB MOLBIOL.…”
Section: Materials and Methods Collection Of Bilementioning
confidence: 99%